Evolutionary insights into porcine genomic structural variations based on a novel‐constructed dataset from 24 worldwide diverse populations. (9th August 2022) - Gong, Huanfa; Liu, Weiwei; Wu, Zhongzi; Zhang, Mingpeng; Sun, Yingchun; Ling, Ziqi; Xiao, Shijun; Ai, Huashui; Xing, Yuyun; Yang, Bin; Huang, Lusheng
Abstract: Structural variations (SVs) are important DNA polymorphisms that contribute to genetic diversity and evolution in humans, animals, and plants. In this study, we present a novel swine SV dataset of 79, 919 deletions, 23, 638 duplications, and 9333 inversions with average sequence depths of 24.1× from 24 varieties of worldwide pig populations, encompassing 305 individuals. Genotypes of SVs, particularly deletions, can accurately group individuals based on their population identity. We showed that exon‐covering deletions were subject to negative selection. Fixation index and differential allele frequency analysis identified highly differentiated SVs between European and Asian indigenous pigs, including deletions in NR6A1 and PLAG1, which are significantly associated with vertebrate numbers and growth performances, respectively. The growth‐enhancing allele at the deletion in PLAG1 was shared by European commercial pigs and Northern Chinese indigenous pigs including Laiwu and Min pigs, suggesting potential introgression from European commercial breeds into Chinese indigenous breeds. Moreover, we uncovered highly differentiated SVs in 139 genes between domesticated pigs and wild boars in Asia, temperature and altitude adaptation‐associated SVs in 41 genes, and population‐specific SVs in 718 genes. This study provides novel insights into the role of porcine SVs in domestication, environmental adaptation, and breed formation.